2013
DOI: 10.1371/journal.pone.0065467
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance in Natural Isolates of Leishmania donovani s.l. Promastigotes Is Dependent of Pgp170 Expression

Abstract: Resistance of pathogens to drugs is a growing concern regarding many diseases. Parasites like Leishmania, Plasmodium and Entamoeba histolytica; and neoplastic cells, present the multidrug-resistant phenotype rendering chemotherapy ineffective. The acquired resistance of Leishmania to antimony has generated intense research on the mechanisms involved but the question has not yet been resolved. To test the hypothesis that drug efflux in Leishmania, as measured by flow cytometry using the fluorescent dye Rhodamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 49 publications
0
17
1
13
Order By: Relevance
“…Messaritakis and others 18 related the efflux rate of Leishmania isolates to the number of Pgp molecules, using the C219 monoclonal antibody, and found them, consistently, to be higher in the isolates with a higher rate of efflux, as shown by FCM. This was also true for the isolates if they were exposed to Glucantime as a result of which, the number of pumps as well as the efflux rate of the isolates, increased.…”
Section: 41mentioning
confidence: 87%
See 4 more Smart Citations
“…Messaritakis and others 18 related the efflux rate of Leishmania isolates to the number of Pgp molecules, using the C219 monoclonal antibody, and found them, consistently, to be higher in the isolates with a higher rate of efflux, as shown by FCM. This was also true for the isolates if they were exposed to Glucantime as a result of which, the number of pumps as well as the efflux rate of the isolates, increased.…”
Section: 41mentioning
confidence: 87%
“…16 It has been shown that Leishmania, under arsenite and methotrexate selection, overamplifies and expresses genes (e.g., ItpgpA) that are part of the gene family encoding the Pgp. 18,[36][37][38] A member of this gene family (ldmdr1) can induce a drug-resistant phenotype in Leishmania 39 and has been molecularly characterized in L. donovani.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations